2017
DOI: 10.1017/s0950268817000887
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of diagnosed pertussis among individuals with asthma or chronic obstructive pulmonary disease in the USA: an analysis of administrative claims

Abstract: SUMMARYIndividuals with chronic respiratory conditions may be at increased risk for pertussis. We conducted a retrospective administrative claims analysis to examine the incidence and economic burden of diagnosed pertussis among adolescents and adults in the USA with chronic obstructive pulmonary disease (COPD) or asthma. Patients aged ⩾11 years with diagnosed pertussis and pre-existing COPD (n = 343) or asthma (n = 1041) were matched 1:1 to patients with diagnosed pertussis but without COPD or asthma. Differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 24 publications
4
63
0
1
Order By: Relevance
“…Outbreaks of pertussis have been reported periodically every two to five years, mainly in adolescents and adults 11. Overweight or obese people and those with pre-existing respiratory conditions such as chronic obstructive pulmonary disease (COPD) or asthma are at increased risk 121314…”
Section: How Common Is It?mentioning
confidence: 99%
“…Outbreaks of pertussis have been reported periodically every two to five years, mainly in adolescents and adults 11. Overweight or obese people and those with pre-existing respiratory conditions such as chronic obstructive pulmonary disease (COPD) or asthma are at increased risk 121314…”
Section: How Common Is It?mentioning
confidence: 99%
“…The study analyzed records from a large group of eligible patients who had been diagnosed with pertussis and had pre-existing asthma or COPD and compared these to records from individuals diagnosed with pertussis but without asthma or COPD. 34 The salient findings of this study 34 on the number of diagnosed pertussis among adolescents and adults with preexisting COPD or asthma are summarized in Table 1.…”
Section: Clinical Evidence On the Association Of Copd And Pertussismentioning
confidence: 93%
“…Summary of the findings from a United States retrospective cohort study evaluating the incidence and economic burden of diagnosed pertussis in individuals with COPD or asthma. 34 a) Incidence of diagnosed pertussis among adolescents and adults with pre-existing COPD or asthma Diphtheria and tetanus pathologies are mediated by their respective bacterial toxins. Since tetanus is directly acquired from the environment, herd immunity is not possible although in some countries, maternal immunization protecting infants during the neonatal period is recommended.…”
Section: Pertussis Diphtheria and Tetanus In Italymentioning
confidence: 99%
“…24 Asthma Three studies have shown that individuals with underlying asthma are at increased risk of pertussis diagnosis compared to individuals without, as further illustrated by two case studies ( Figure 3). [28][29][30][31][32] A retrospective, population-based case-control study compared the history of asthma in children and adults who had pertussis (confirmed by polymerase chain reaction, PCR) with age-and sex-matched controls during a pertussis outbreak between 2004 and 2005 in California, USA. Of the 164 cases, 38% had asthma before the pertussis diagnosis compared to 26% of the 328 controls, resulting in an adjusted odds ratio of 1.73 (95% confidence interval [CI]: 1.12-2.67, P = .013).…”
Section: Includedmentioning
confidence: 99%